2020
DOI: 10.3389/fpsyg.2020.562450
|View full text |Cite
|
Sign up to set email alerts
|

More Than (Single) Text Comprehension? – On University Students’ Understanding of Multiple Documents

Abstract: The digital revolution has made a multitude of text documents from highly diverse perspectives on almost any topic easily available. Accordingly, the ability to integrate and evaluate information from different sources, known as multiple document comprehension, has become increasingly important. Because multiple document comprehension requires the integration of content and source information across texts, it is assumed to exceed the demands of single text comprehension due to the inclusion of two additional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
0
11
1
4
Order By: Relevance
“…Furthermore, while not an explicit part of our investigation, one might have expected that proximal behavioral indicators mediate the effect of distal cognitive skills on performance (see Hahnel et al 2017)-a reasonable view from a general perspective on item processing. However, current theories of MD reading do not provide indication for a full mediation effect involving readingrelated skills as predictors and MD-specific behaviors as mediators (for an overview of theoretical perspectives on MDC, see Mahlow et al 2020). Our results also indicate against such a mediating effect.…”
Section: Automated and Controlled Processing In Multiple Document Readingcontrasting
confidence: 74%
See 3 more Smart Citations
“…Furthermore, while not an explicit part of our investigation, one might have expected that proximal behavioral indicators mediate the effect of distal cognitive skills on performance (see Hahnel et al 2017)-a reasonable view from a general perspective on item processing. However, current theories of MD reading do not provide indication for a full mediation effect involving readingrelated skills as predictors and MD-specific behaviors as mediators (for an overview of theoretical perspectives on MDC, see Mahlow et al 2020). Our results also indicate against such a mediating effect.…”
Section: Automated and Controlled Processing In Multiple Document Readingcontrasting
confidence: 74%
“…We fitted a Partial Credit Model (n = 506 cases) with the R package TAM (Robitzsch, Kiefer, and Wu 2019) and obtained Weighted Likelihood Estimates (WLEs) as indicator of students' reading comprehension (WLE reliability = .71). A previous study demonstrated that the NEPS reading comprehension and the MDC test assess highly correlated, but independent skills (Mahlow et al 2020).…”
Section: Reading Comprehensionmentioning
confidence: 98%
See 2 more Smart Citations
“…übereinstimmen. Erste Forschungsergebnisse hierzu konnten bereits Mahlow et al (2020) generieren, die aufzeigen, dass basierend auf dem MDC-Test von Schoor et al (2020) und dem (ergebnisorientierten) Lesekompetenztest des Nationalen Bildungspanels (NEPS) bei n = 501 Student*innen zweier deutscher Universitäten die MDC-Fähigkeiten von der erfassten Lesekompetenz empirisch getrennt werden können. Die statistischen Modellierungen legen K hierbei nahe, dass die MDC-Anforderungen und die Lesekompetenz weder durch einen gemeinsamen Faktor noch durch die Annahme, dass MDC-Fähigkeiten auf die Lesekompetenz aufbauen, erklärt werden können.…”
Section: Diskussionunclassified